PETRAS VILEIŠIS RELATIONS WITH MARTYNAS JANKUS (1883–1894) - ANIČAS, JONAS (Knygotyra, 2015)
Petras Vileišis was a prominent figure in the history of Lithuania in late 19th and early 20th century. Particular role in his educational activities belongs to Martynas Jankus – a printer, publisher and cultural worker of national movement of Lithuania Minor. In 1883–1894 M. Jankus published the greater part of educational books and booklets written by P. Vileišis, all in all about 15 000 copies. They were distributed in towns and villages by covert book Abstracthawkers. Productive cooperation of these two distinguished personalities helped to mature the movement of national rebirth of Lituania. This is evident from Petras Vileišis letters to Martinas Jankus, which are in the custody of the Manuscript Department of the Library of Vilnius University. Unfortunately the fate of Martynas Jankus letters to Petras Vileišis is not known.